Co-occurrence of myositis and neuropathy after anti-CD30 therapy in a late-adolescent Hodgkin lymphoma patient - Adela Della Marina; Lydia Rink; Andreas Hentschel; Michael M. Schündeln; Christopher Nelke; Heike Kölbel; Calvin Tucht; Vera Dobelmann; Tobias Ruck; Tim Hagenacker; Teresinha Evangelista; Ulrike Schara-Schmidt; et al. (Acta Neuropathologica Communications, 2025)
Abstract Objective Immune-related adverse events (irAEs) are recognized in oncology, particularly with immune checkpoint inhibitors and other targeted therapies. Brentuximab Vedotin (BV), is an anti-CD30 antibody–drug conjugate- its association with immune-mediated myositis remains unexplored. We report a case of an adolescent with Hodgkin lymphoma (HL) who developed neuropathy and myositis following BV therapy. Materials & methods The diagnostic work-up included MRI as well as microscopic analyses (histology, electron microscopy, and immunostainings including CD30 and MxA) of a gastrocnemius muscle biopsy. Proteomic analysis was also performed on the same biopsy, and paradigmatic protein dysregulations were validated through immunostaining. Serum NCAM1 levels were measured using ELISA. Results The patient, diagnosed with HL at 15 years, developed neuropathy after Vincristine treatment and was switched to BV. During BV therapy, she experienced progressive muscle weakness and foot drop, leading to discontinuation. MRI confirmed myositis, and biopsy revealed neurogenic and inflammatory changes with complement deposition and mitochondrial dysfunction. Proteomics showed upregulation of inflammatory relevant proteins, with HPRT1 (749.43-fold) being the most increased one. Intravenous immunoglobulin (IVIG) therapy improved muscle strength. Discussion Myositis following BV therapy has not been reported. Findings suggest an immune-mediated mechanism with B-cell involvement. Given the response to IVIG, B-cell-directed therapies may be beneficial. This case identifies BV-induced myositis as a novel irAE.